Analisis Break Even Point Penjualan Pupuk Organik (Studi Kasus Simantri 174 Gapoktan Dharma Pertiwi di Kabupaten Badung, Provinsi Bali) - CEMPAKA, MEGA DUTHA; DEWI, RATNA KOMALA; WULANDIRA SDJ, A.A.A. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Analysis Sales of Break Even Point Organic Fertilizer (Case Study Simantri 174 Gapoktan Dharma Pertiwi in Badung Regency, Province Of Bali) Organic fertilizer industry in Indonesia generally consists of small and medium businesses. The difference of the number of the needs and the production of organic fertilizer is a beneficial business opportunity. One of them is Simantri 174 Gapoktan Dharma Pertiwi. Analysis of the break even point is a situation where the company does not suffer losses also didn't get the profit. Commonly, this analysis gives information about margin of safety to the management of how much the decrease of the selling can be reckoned so that the company will not having a loss. The purpose of this research is to know the amount and value of sales of organic fertilizer Simantri 174 which must be achieved at the point of BEP and the margin of safety of the sale. The data period used is one year that is year 2014. According to the research result, the level of BEP that is accomplished by Simantri 174 is 509.763,14 kg (Rp 458.993.308,66). Margin of safety Simantri worked with the level of safety is 37,44 %. It can be concluded that the decrease of the organic fertilizer selling could not be more than 37,44 (Rp 274.735.791,34) from the planning. Simantri 174 has successfully produced organic fertilizer above the BEP value. Aside from that, there are some technical problems such as lack of basic materials; the dryer for the basic material is not yet available and lack of training of MOL producing. As well as the presence of obstacles in the economic aspect, namely the lack of costs for the production process of organic fertilizer. Keywords: break even point, margin of safety, organic fertilizer, sales.